Congenital Unilateral Hypoplasia of Depressor Anguli Oris. (17th September 2012) - Ulualp, Seckin O.; Deskin, Ronald
Abstract : Objectives . Asymmetric facial appearance may originate from abnormalities of facial musculature or facial innervation. We describe clinical features of congenital hypoplasia of depressor anguli oris muscle in a child. Material and Methods . Chart of a 10-month-old female referred to a tertiary care pediatric hospital for assessment of facial paralysis was reviewed. Data included relevant history and physical examination, diagnostic work up, and management. Results . The child presented with asymmetric movement of lower lip since birth. Asymmetry of lower lip was more pronounced when she smiled and cried. Rest of the face movement was symmetric. On examination, the face appeared symmetric at rest. The child had inward deviation of right lower lip when she smiled. Facial nerve function, as determined by frowning/forehead, wrinkling, eye closure, nasolabial fold depth, and tearing, was symmetric. Magnetic resonance imaging of the temporal bones and internal auditory canals were within normal limits. Echocardiogram did not show cardiac abnormality. Auditory brainstem response showed no abnormality. Conclusions . Congenital hypoplasia of depressor anguli oris is a rare anomaly that causes asymmetric crying face. Pediatricians and otolaryngologists need to be cognizant of cardiac, head and neck, and central nervous system anomalies associated with congenital unilateral hypoplasia of depressor anguli oris.